Electrocatalytic Generation of Amidyl Radicals for Olefin Hydroamidation: Use of Solvent Effects to Enable Anilide Oxidation. (6th January 2016) - Zhu, Lin; Xiong, Peng; Mao, Zhong‐Yi; Wang, Yong‐Heng; Yan, Xiaomei; Lu, Xin; Xu, Hai‐Chao
Abstract: Oxidative generation of synthetically important amidyl radicals from N−H amides is an appealing and yet challenging task. Previous methods require a stoichiometric amount of a strong oxidant and/or a costly noble‐metal catalyst. We report herein the first electrocatalytic method that employs ferrocene (Fc), a cheap organometallic reagent, as the redox catalyst to produce amidyl radicals from N ‐aryl amides. Based on this radical‐generating method, an efficient intramolecular olefin hydroamidation reaction has been developed.